2005
DOI: 10.1016/j.jcrysgro.2005.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of calcium on struvite crystal size, shape and purity

Abstract: Struvite precipitation occurs spontaneously in wastewater treatment plants under conditions that are influenced by many factors including concentration of PO ions, pH, temperature and mixing energy. These parameters are often difficult to control and as a result struvite generates problems of scale deposits in areas such as pipes and recirculation pumps. At the same time, struvite is considered as a potentially marketable product as an alternative fertiliser. For those two reasons, it has become important to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
228
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(248 citation statements)
references
References 14 publications
13
228
0
7
Order By: Relevance
“…Calcium ions actively react with phosphate to form calcium phosphates. Previous studies on the influence of calcium on struvite crystallization reported that Calcium ions with struvite co-precipitation can retard the nucleation induction and inhibit the growth for struvite crystal formation 6,7 . However, calcium, as an impurity, could be a negative factor for struvite formation.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions actively react with phosphate to form calcium phosphates. Previous studies on the influence of calcium on struvite crystallization reported that Calcium ions with struvite co-precipitation can retard the nucleation induction and inhibit the growth for struvite crystal formation 6,7 . However, calcium, as an impurity, could be a negative factor for struvite formation.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions can actively react with phosphate to form calcium phosphates. Previous works on the effects of calcium on struvite crystallization reported that calcium ions with struvite co-precipitation may retard the nucleation induction and inhibit the growth of struvite crystal formation (Le Corre et al, 2005). Moreover, calcium, as an impurity, could be a negative factor of struvite formation.…”
Section: Discussion Chemical Equilibrium Model and Mineral Speciatiomentioning
confidence: 99%
“…As a consequence of obstruction for crystallisation of struvite, the change in the characteristics of struvite crystals may occur, however this area of research has not been examined in detail in terms of qualitative and quantitative. Thus only limited study has been conducted in this area of research (Le Corre et al, 2005). Here, an improved understanding on struvite precipitation out a solution due to the presence of ion additives is required.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is that organic matter could bind to ions, thereby affecting ionic activity (Ronteltap et al, 2010;Udert et al, 2003). It was found that increasing the calcium concentration reduces crystal size and inhibits struvite growth, or affects struvite crystallization and leads to the formation of an amorphous substance rather than crystalline struvite (Le Corre et al, 2005). Lower MWt matters undergo complexation with calcium, and inhibit the competitive effect with Mg 2+ toward PO 4 3− .…”
Section: Precipitant Characteristicsmentioning
confidence: 99%